Translating Mrs. Dalloway : from German to Urdu, 1928-2024: NONE - Dubino, Jeanne (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2026)
From the time Mrs. Dalloway was first published in 1925, it has been a global novel. Within three years of its publication, it was translated into German, and through the decades the number of different translations has grown. By the hundredth anniversary of its publication, it was translated into 42 languages, with the latest, Urdu, in 2024. One cannot overestimate the crucial role that translators have played in making Mrs. Dalloway such a global phenomenon. Along with further describing its global presence via translations, I explore the vital importance of translators and the many dimensions of translation, especially in the context of Mrs. Dalloway alone. Woolf was interested in these many dimensions and undertook translations herself, even during the writing of Mrs. Dalloway. She was aware of the protean receptions of translations. Next, I trace some of the ways that the translations of Mrs. Dalloway in multiple regions and through the decades have been received. Translation, of course, does not function alone; it is part of a larger process that includes variables like paratexts and facets of the publishing industry. Translation itself is, of course, a complicated endeavor involving myriad vectors; to examine Mrs. Dalloway within the discipline of Translation Studies is to show the complexity of these considerations. Finally, examining some of the translations of Mrs. Dalloway is to show that there are issues peculiar to this novel alone, as the rich field of criticism on the translations of this novel shows. --- TRADUZINDO MRS. DALLOWAY: DO ALEMÃO AO URDU, 1928-2024 Desde a sua primeira publicação em 1925, Mrs. Dalloway tornou-se um romance global. Em apenas três anos, foi traduzido para o alemão e, ao longo das décadas, o número de traduções só aumentou. No centenário da sua publicação, já havia sido traduzido para 42 idiomas, sendo o urdu a tradução mais recente, em 2024. Não se pode subestimar o papel crucial que os tradutores desempenharam na transformação de Mrs. Dalloway num fenômeno global. Além de descrever a sua presença mundial através das traduções, exploro a importância vital dos tradutores e as múltiplas dimensões da tradução, especialmente no contexto de Mrs. Dalloway. Woolf interessava-se por estas dimensões e realizou traduções ela própria, mesmo durante a escrita de Mrs. Dalloway. Estava ciente da mutabilidade das traduções na sua recepção. Em seguida, analiso algumas das formas como as traduções de Mrs. Dalloway foram recebidas em diversas regiões e ao longo das décadas. A tradução, naturalmente, não funciona isoladamente; faz parte de um processo mais amplo que inclui variáveis como paratextos e aspectos da indústria editorial. A tradução em si é, sem dúvida, uma tarefa complexa que envolve inúmeros fatores; examinar Mrs. Dalloway dentro da disciplina de Estudos da Tradução é demonstrar a complexidade dessas considerações. Por fim, examinar algumas das traduções de Mrs. Dalloway é mostrar que existem questões peculiares a este romance, como demonstra o vasto campo da crítica literária sobre as traduções desta obra. --- Original em inglês.